The Role of the Village Head in the Implementation of Development in Tual City, Pulau Dullah Utara District, Ohoitahit Village - Purnomo, Hari; Suljatmiko, Suljatmiko (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Indonesian culture mainly exists in rural areas. Therefore, what must be considered in development work and village development is the government's priority. The village government itself is the official government of the village community unit. As one of the lowest governmental powers, the village level government does not only have the power or power to manage its own affairs (village level autonomy). But also has decentralized and superior power level government. Where the village is the location of all offices for all elements of the community unit in the village. Achieving village development goals is an important part of development. This means that the village head as the coordinator and implementer of village level development led by the village head delegates responsibility for implementation and development to the village head. Ohoitahit Village was chosen as the sample because its physical development lags behind other villages in Jalan Tual Village. North Dura Island. Ohhoitahit Village. A development plan was drawn up for the town of Tual in the area. A 30 kilometer long road is planned to be built on North Dura Island in Ohhoitahit Village at a cost of Rp. 1,000,000,000 - up to Rp. The construction of this junior high school requires a capital of Rp. 30 million. 750,000,000. In addition, the target for MDA development is Rp. 200,000,000, - has not been implemented. In addition, information on PLTD is Rp. 250 million were not completed according to plan, and the village information planning objective explained that 204 households were not completed as planned.